1969
DOI: 10.1111/j.1365-2141.1969.tb05669.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Chromosomal Studies in First‐Degree Relatives of Children with Acute Lymphoblastic Leukaemia

Abstract: Summary . Immunoglobulins (IgG, IgM and IgA) were estimated in sera from mothers and siblings of children with acute lymphoblastic leukaemia (ALL) and in sera from appropriate controls. The distribution of IgA titres was significantly lower in the siblings of leukaemic children than in control children and that of IgM was significantly higher in mothers of leukaemic children than in control mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1

Year Published

1972
1972
1980
1980

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
(13 reference statements)
1
12
1
Order By: Relevance
“…As it is impossible to distinguish between immunodeficiency of genetic origin and that resulting from the leukaemia or its treatment in the patients themselves, attempts have been made to uncover predisposing genetic immunodeficiency by studying the patients' relatives. Results of leucocyte counts, immunoglobulin estimations and lymphocyte transformation tests in the parents of children with leukaemia have shown no consistent differences from controls (Sutton et al, 1969;Chandra, 1972;Evans, 1973;Hann et al, 1975), but these measures are very crude indicators of immune function.…”
mentioning
confidence: 99%
“…As it is impossible to distinguish between immunodeficiency of genetic origin and that resulting from the leukaemia or its treatment in the patients themselves, attempts have been made to uncover predisposing genetic immunodeficiency by studying the patients' relatives. Results of leucocyte counts, immunoglobulin estimations and lymphocyte transformation tests in the parents of children with leukaemia have shown no consistent differences from controls (Sutton et al, 1969;Chandra, 1972;Evans, 1973;Hann et al, 1975), but these measures are very crude indicators of immune function.…”
mentioning
confidence: 99%
“…In the present family it appears that the IgA deficiency was inherited from the mother (I 2) and was not a simple dominant characteristic. That this association between inherited leukaemogenic factors and immunodeficiencies might not be fortuitous is suggested by the work of Sutton et al (1969), who found lower concentrations of IgA in siblings of leukaemic children. Further evidence is provided by the numerous reported cases of the association of lymphoreticular malignancy and cellular and humoral immunodeficiency (Freeman et al, 1970;Galton and Spiers, 1971;Potolsky et al, 1971).…”
mentioning
confidence: 99%
“…In a different, but analogous, experimental situation such an activation of an endogenous, vertically transmitted, RNA tumour virus by a DNA virus has been demonstrated by Rhim and Huebner (1973). In man, some indirect evidence exists for the presence of such a vertically transmitted agent, in that raised IgM levels have been detected in neonatal sibs of children with leukaemia (Sutton, Bishun, and Soothill, 1969;Chandra, 1972).…”
Section: Discussionmentioning
confidence: 94%